Retifanlimab Vs Avelumab in Patients with Metastatic Merkel Cell Carcinoma: A Cost Utility Analysis in Italy - Ghetti, Gianni; Porta, Camilla; Povero, Massimiliano (Farmeconomia. Health Economics and Therapeutic Pathways, 2025)
OBJECTIVE: Merkel cell carcinoma (MCC) is a very rare and aggressive neuroendocrine skin cancer, characterized by a 5-year survival rate of 13.5% in patients with distant metastases. This study aimed to evaluate the cost-utility of retifanlimab compared to avelumab in the treatment of metastatic MCC patients who had not received prior systemic therapies, from the perspective of the Italian National Health Service (SSN). METHODS: A 7-day cycles partitioned survival model with three mutually exclusive health-states—progression-free, post-progression and death—was developed to compare lifetime clinical outcomes and costs for patients treated with retifanlimab versus avelumab in the Italian context. Progression-free survival and overall survival curves were modelled independently, with POD1UM-201 trial data used for retifanlimab efficacy. In the absence of direct head-to-head clinical trial data, avelumab efficacy was estimated using the hazard ratio obtained from a matching-adjusted indirect comparison. Following a previous National Institute for Health and Care Excellence submission, utility values were derived using a timeto-death approach, with health states defined as “>266 days to death”, “35-266 days to death”, and “<35 days to death”. Direct healthcare costs, including drug acquisition and administration, disease monitoring, adverse event management, post-progression therapy, and end-of-life care, were sourced from Italian data. Costs and health outcomes were discounted at an annual 3% rate. Deterministic and probabilistic sensitivity analyses, along with scenario analysis, were conducted to assess the uncertainty of input parameters. RESULTS: In the base case, retifanlimab demonstrated greater efficacy compared to avelumab, with 6.39 vs 3.42 life-years and 5.11 vs 2.68 quality-adjusted life-years (QALYs), at an additional cost of €12,228. The incremental cost-utility ratio was estimated at €5,037 per QALY gained. Sensitivity analyses confirmed the robustness of the base case results. CONCLUSIONS: Retifanlimab can be considered a cost-effective option for Italian patients with metastatic MCC who have not received prior systemic therapies.